Effectiveness of the application of instructional media using the Canva application in marketing subjects at SMK 45 Lembang - Diah Putri Nunirmala; Hamdan Rachmatulah; Senny Alfia (Curricula: Journal of Curriculum Development, 2024)
Applying learning media in vocational schools certainly requires creativity and mastery of technology which must be possessed by every educator. Media in the learning system has an important role that should not be ignored. Descriptive quantitative research conducted at SMK 45 Lembang aims to measure the effectiveness of using the Canva application in learning to improve student learning outcomes because students are more motivated to participate in learning related to technology they are already familiar with, such as Android, WhatsApp, and Instagram. 1) In the context of using Canva as a learning medium in Marketing subjects at vocational high schools (SMK), its implementation is not optimal because most educators are not yet proficient in this technology. The use of learning media through Canva has not gone well, with most educators still relying on books as teaching materials, applying the lecture method, and only presenting material in written form, which makes students feel bored. 2) Obstacles faced by educators include lack of mastery of technology, limited facilities and media, and lack of creativity in creating teaching materials. 3) The application of Canva as a learning medium was successful in helping students understand marketing subjects.